Population study of orofacial injuries in adult family violence homicides in Victoria, Australia. (November 2020) - Sarkar, Reena; Ozanne-Smith, Joan; Dipnall, Joanna F.; Bassed, Richard
Highlights: Whole population study of orofacial injuries in adult family violence homicides. Recognition of significant patterns and sentinel nature of orofacial injuries in the context of clinical parameters. Orofacial injuries may function as a marker of nonfatal and future family violence in Victoria. Abstract: Background: This study describes the prevalence and orofacial injury patterns associated with adult family violence (FV) homicides in Victoria, Australia. It follows a methods study for case selection of all FV homicides and injury measurement. Comprehensive analysis of orofacial injuries in FV homicides and their clinico-demographic context will inform future research on clinical FV indicators and sentinel injuries, and potentially lead to premorbid intervention in health services. Methods: All closed cases of FV homicides aged ≥18 years, January 2006 to December 2018, were identified by screening Victorian fatal assaults, based on victim-offender relationship. Primary data such as post-mortem computed tomography scans and photographs were assessed. Socio-demographic, clinical, interpersonal and incident parameters were descriptively analysed and statistically compared across FV homicides with and without facial injuries using cluster analysis and nonparametric tests. Results: Of 170 adult homicides screened for eligibility, 151 were included for final analysis. Over the 12-year period, 78.1% of all Victorian adult FV homicides had orofacial injuries. Significant cluster patterns of injury mechanism, victim-offender relationship and drug/alcohol impairment were identified in all homicides. Non-facial injuries were significantly higher in facial vs. non-facial injury homicides. Facial abrasion and incised wounds were the most common injury types. Conclusions: This is the first forensic-epidemiologic study evaluating the empirical evidence concerning orofacial injuries associated with population-wide adult Victorian FV homicides. The high level of orofacial injuries in this population during the study period may inform clinical practice and policy in FV intervention in Victoria and globally.